Can adaptive expertise, reflective practice, and activity theory help achieve systems-based practice and collective competence? - Orsino, Angela; Ng, Stella (Revue canadienne de l'éducation médicale, 2019)
Physicians must function as integral members of the complex social systems in which they work to support the health of their patients; competency-based education frameworks describe this function of physicians in terms of systems-based practice, advocacy, and collaboration. Yet education for these social competencies continues to present challenges, perhaps because medical education has tended to focus less on social systems and more on traditional healthcare systems. In this paper, we use a clinical example from the discipline of Developmental Pediatrics, that of early identification of autism spectrum disorder (ASD), as an illustration of a socially complex zone of practice necessitating systems-based practice. We first explore this practice context through the framings of collective competence and activity theory to represent the complex practices and systems involved in identifying ASD. We then align these framings of the practice context and complexity with two bodies of education theory, adaptive expertise and reflective practice. We argue that these approaches to education will prepare learners to be more aware of and responsive to the dynamic needs of the complex and intersecting systems in which they will practice.